Macroeconomic Gains from Reforming the Agri-Food Sector : The Case of France - Batini, Nicoletta (Washington, D.C. : International Monetary Fund, 2019)
France is the top agricultural producer in the European Union (EU), and agriculture plays a prominent role in the country's foreign trade and intermediate exchanges. Reflecting production volumes and methods, the sector, however, also generates significant negative environmental and public health externalities. Recent model simulations show that a well-designed shift in production and consumption to make the former sustainable and align the latter with recommended values can curb these considerably and generate large macroeconomic gains. I propose a policy toolkit in line with the government's existing sectoral policies that can support this transition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet